Example of design space reduction method using Intelligence partitioning - Shallari, Irida (Mid Sweden University, 2021)
This zip folder contains the MatLab code that can be used during design space exploration to identify optimisation areas for a given design case. Based on a preliminary set of data such as an estimate of the number of operations, an energy constraint, and the intermediate data volume between the processing stages, we can use this tool to identify areas where optimisation efforts would provide the highest impact on the node energy efficiency.

The dataset was originally published in DiVA and moved to SND in 2024.
Example of design space reduction method using Intelligence partitioning
Keywords: design space reduction; design space reduction; IoT; IoT; Inteligence partitioning; Inteligence partitioning; Embedded Systems; Inbäddad systemteknik